2008
DOI: 10.1097/mpg.0b013e31816fee95
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Treatment of Primary Sclerosing Cholangitis in Children With Oral Vancomycin: An Immunomodulating Antibiotic

Abstract: Before this study, there has not been an effective long-term treatment for sclerosing cholangitis to prevent the usual progression of this disease to cirrhosis. This study showed that oral vancomycin could be an effective long-term treatment of sclerosing cholangitis in children, especially those without cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
109
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 29 publications
7
109
0
1
Order By: Relevance
“…7 A few studies have suggested a clinical benefit of treatment with vancomycin in PSC children with IBD, 23 and especially those without cirrhosis. 24 No patients in our series were taking this antibiotic.…”
Section: Treatment Clinical Course and Prognosismentioning
confidence: 99%
“…7 A few studies have suggested a clinical benefit of treatment with vancomycin in PSC children with IBD, 23 and especially those without cirrhosis. 24 No patients in our series were taking this antibiotic.…”
Section: Treatment Clinical Course and Prognosismentioning
confidence: 99%
“…In addition, when vancomycin treatment was discontinued, there was recurrence of clinical symptoms and an increase in liver enzymes in several patients and re-treatment again resulted in normalisation of liver enzymes. 27 Most recently, in a pilot study by Silveira et al, 16 patients with PSC were treated with minocycline for one year; although a substantial proportion of patients withdrew from the study due to AEs, those who continued treatment were found to experience a significant reduction in ALK. 39 Although the use of antibiotics in PSC seems logical and promising based on the clinical experience described above, there is very little data on humans supporting their role in the pathophysiology of this disease.…”
mentioning
confidence: 99%
“…[27][28][29][30] Aminotransferase values are independently associated with prognosis and are a component of the Months of treatment and follow-up are absolute unless otherwise indicated. Mayo PSC risk score, and ALK values have been recently associated with prognosis, 31 thus making these two readily measured liver biochemistries important end points in studies of PSC.…”
mentioning
confidence: 99%
“…One underpowered, double-blind, controlled study of oral vancomycin as add-on treatment to intravenous steroids in 33 adult patients with acute severe colitis reported a lower numerical rate of short-term colectomy in the vancomycin arm (11%) vs. placebo (47%; p = 0.057) [8]. In a few case series and one small controlled study, vancomycin has been found to improve PSC [4,5,8,9,10]. Two of these studies were in children and reported that the IBD-related symptoms also improved in all patients; those patients who underwent repeat colonoscopy showed endoscopic resolution or improvement [4,5].…”
Section: Discussionmentioning
confidence: 99%